ORC6, Negatively Regulated by miR-1-3p, Promotes Proliferation, Migration, and Invasion of Hepatocellular Carcinoma Cells - Chen, Hu; Bao, Lequn; Hu, Jianhua; Wu, Dongde; Tong, Xianli (Frontiers in Cell and Developmental Biology, 2021)
Background: In recent years, microRNA-1-3p (miR-1-3p), has been linked to the progression of multiple cancers, whereas, little is known about its role in hepatocellular carcinoma (HCC). Herein, we investigated the expression characteristics, function of miR-1-3p in HCC, and its regulatory function on origin recognition complex subunit 6 (ORC6). Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was performed for detecting the expression levels of miR-1-3p and ORC6 mRNA in HCC samples and cell lines. ORC6 expression at protein level was quantified by Western blot. After gain-of-function and loss-of-function models were established, cell counting kit-8 (CCK-8) assays, Transwell assays, flow cytometry and 5-Ethynyl-2'-deoxyuridine (EdU) assay were performed for examining cell proliferation, migration, invasion, cell cycle and apoptosis. Targeting relationship between miR-1-3p and ORC6 was confirmed with bioinformatic analysis and dual-luciferase reporter assays. Results: The expression of miR-1-3p was reduced in HCC samples and cell lines. Overexpression of miR-1-3p suppressed the proliferation, migration, and invasion, and induced cell-cycle arrest and apoptosis of HCC cells, whereas the opposite effects were induced by miR-1-3p inhibition. ORC6 is identified as a novel target of miR-1-3p, the expression of which is negatively correlated with miR-1-3p expression in HCC tissues. ORC6 overexpression facilitated the proliferation, migration, invasion, and cell cycle progression, and reduced apoptosis of HCC cells, whereas the opposite effects were induced by ORC6 knockdown. What’s more, ORC6 overexpression counteracted with the biological functions of miR-1-3p in HCC cells. Conclusion: MiR-1-3p targets ORC6 to suppress the progression of HCC.